THE EFFECT OF PARENTS' EDUCATION LEVEL AND EDUCATIONAL GAME TOOLS ON SOCIAL EMOTIONAL DEVELOPMENT - Astuti Lidya; Ahmad Suriansyah; Aslamiah Aslamiah (Universitas Lambung Mangkurat, 2022)
Family is the first environment that requires children to be able to adjust well in line with their age and maturity. parents have a big role to play in impacting a child's education. The future of the child will depend heavily on the experience gained by the child including educational factors and parenting patterns in providing play facilities to the child, the parenting pattern is a process of interaction that occurs between parents and children that affects the development of the child's personality. This study aims to analyze the influence of education level, parenting patterns and educational game tools on the social and emotional development of kindergarten A Se Gugus Melati group in West Banjarmasin. This type of research method is quantitative research conducted in TK Melati Cluster West Banjarmasin district with a population of 361. The samples were taken with stratified random sampling techniques as many as 190 respondents of parents. Data collection techniques are carried out using questionnaire methods that are tested for validity using the moment product correlation coefficient technique. Data analysis uses descriptive and path analysis, data processing using SPSS version 16.0. The results of the study: (1) There is a direct influence between the level of parenting and educational game equipment on the social and emotional development of group A children in TK Cluster Melati West Banjarmasin Subdistrict. (2) There is no indirect influence of education level through foster pattern and education level through educational game tools on the emotional social development of group A children in kindergarten Of Melati Group of West Banjarmasin Subdistrict